2013
DOI: 10.1152/jn.00288.2013
|View full text |Cite
|
Sign up to set email alerts
|

Medullary serotonin neurons are CO2 sensitive in situ

Abstract: Brainstem central chemoreceptors are critical to the hypercapnic ventilatory response, but their location and identity are poorly understood. When studied in vitro, serotonin-synthesizing (5-HT) neurons within the rat medullary raphé are intrinsically stimulated by CO2/acidosis. The contributions of these neurons to central chemosensitivity in vivo, however, are controversial. Lacking is documentation of CO2-sensitive 5-HT neurons in intact experimental preparations and understanding of their spatial and propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
47
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 79 publications
9
47
0
3
Order By: Relevance
“…Therefore, Ugt1a6 and Ugt1a7 in the brain may play important roles in detoxification and homeostasis to protect the brain. In the present study, APAP glucuronidation was increased by PB in the dmd.aspetjournals.org medulla oblongata and thalamus, where serotonin, a Ugt1a6 substrate, was found (Iceman et al, 2013;Chung et al, 2015). Thus, the concentrations of UGT substrates, including serotonin, may change locally, thereby altering efficacy.…”
Section: Discussionsupporting
confidence: 44%
“…Therefore, Ugt1a6 and Ugt1a7 in the brain may play important roles in detoxification and homeostasis to protect the brain. In the present study, APAP glucuronidation was increased by PB in the dmd.aspetjournals.org medulla oblongata and thalamus, where serotonin, a Ugt1a6 substrate, was found (Iceman et al, 2013;Chung et al, 2015). Thus, the concentrations of UGT substrates, including serotonin, may change locally, thereby altering efficacy.…”
Section: Discussionsupporting
confidence: 44%
“…As previously reported, 5-HT neurons were chemosensitive to acidosis in culture (Wang et al 1998(Wang et al , 2001Wang and Richerson 1999), and this property was retained in a perfused brain preparation (Iceman et al 2013). In culture and in the perfused brain stem, 1% isoflurane abolished the firing of 5-HT neurons under control conditions and prevented the increase in firing frequency normally induced by hypercapnic acidosis.…”
supporting
confidence: 74%
“…Briefly, the mean interspike interval ( x, in ms) and the SD of the interspike interval (s, in ms) were derived as independent variables and used to solve the discriminant function y͑x , s͒ ϭ 146 ms Ϫ x ϩ 0.98s A value resulting from this function Ͻ0 indicates that the cell is likely to be serotonergic (putative 5-HT cell), while a value Ͼ0 indicates the cell is not likely to be serotonergic. We and others have characterized recordings as putative 5-HT neurons by firing pattern analysis and confirmed that it is accurate at least 90% of the time compared with juxtacellular labeling and immunohistochemical neurotransmitter phenotyping (Iceman et al 2013;Mulkey et al 2004).…”
Section: Identification Of 5-ht Neuronssupporting
confidence: 58%
See 1 more Smart Citation
“…Lesions of serotonergic or the locus coeruleus noradrenergic neurons attenuate the CO 2 -induced arousal and the HCVR but have minimal effects on the hypoxia-induced arousal or the hypoxic ventilatory reflex (13,14,21,41,45). To date, the interpretation of this evidence is that subsets of these aminergic neurons are directly responsive to protons (i.e., central chemoreceptors) and unaffected by hypoxia (20).…”
Section: Discussionmentioning
confidence: 99%